Tahlilan Tradition of the Suka Jaya Village Community in Perspective Islamic Education - Arifin, Muhammad Nur; Wahyuni, Nurfita; Asrori, Mohammad (The Magister of Islamic Education IAIN Pontianak, 2024)
This study examines the role of the tahlilan tradition in Islamic education in Suka Jaya Village. Tahlilan, a local religious ritual for praying for the deceased, holds significant informal educational value for the community. The research shows that through tahlilan activities, the community, particularly the younger generation, learns Islamic teachings such as tauhid (the oneness of God), aqidah (faith), and akhlaq (ethics). In addition to serving as an educational medium, tahlilan also strengthens social bonds and solidarity among the village residents. This tradition reflects a form of acculturation between Islamic teachings and local culture, which has long developed in the archipelago. Despite facing challenges from groups opposing this practice, the majority of Suka Jaya residents continue to uphold tahlilan as part of their religious and social identity. The findings of this research affirm that tahlilan is not only a spiritual ritual but also plays significant social, moral, and educational roles in shaping the Islamic character of the community.